Bounded extremum seeking for angular velocity actuated control of nonholonomic unicycle. (17th August 2016) - Scheinker, Alexander
Summary: We study control of the angular‐velocity actuated nonholonomic unicycle, via a simple, bounded extremum seeking controller which is robust to external disturbances and measurement noise. The vehicle performs source seeking despite not having any position information about itself or the source, able only to sense a noise corrupted scalar value whose extremum coincides with the unknown source location. In order to control the angular velocity, rather than the angular heading directly, a controller is developed such that the closed loop system exhibits multiple time scales and requires an analysis approach expanding the previous work of Kurzweil, Jarnik, Sussmann, and Liu, utilizing weak limits. We provide analytic proof of stability and demonstrate how this simple scheme can be extended to include position‐independent source seeking, tracking, and collision avoidance of groups on autonomous vehicles in GPS‐denied environments, based only on a measure of distance to an obstacle, which is an especially important feature for an autonomous agent. Copyright © 2016 John Wiley & Sons, Ltd.